«Εις τας δροσεράς πηγάς της πρωτογενούς τέχνης». Η πρόσληψη της κρητομυκηναϊκής σφραγιδογλυφίας στο έργο του Κωστή Παρθένη: - ΣΩΤΗΡΙΟΥ ΘΑΝΑΣΗΣ Θ. (Μνήμων, 2012)
Thanassis Th. Sotiriou, “In the cool springs of primordial art”. The perception of Creto-Mycenaean glyptic art in Kostis Parthenis’ oeuvre In the first decades of the 20th century, within the framework of Modernist Primitivism and following the sensational discoveries of Sir Arthur J. Evans in Knossos, Kostis Parthenis was probably the first modern Greek artist to assimilate elements of prehistoric Aegean art in his work.A study of Parthenis’ oeuvre led to the significant observation that the artist incorporated several iconographical and morphological features derived specifically from Creto-Mycenaean glyptic art in paintings dating approximately from the first half of the 1910s to the end of the 1920s.This essay aims to identify references and pinpoint specific prototypes of prehistoric Aegean art in Parthenis’ work. More importantly, an attempt is made at an interpretation of this particular choice through the study of the painter’s views, his artistic course and fundamental characteristics of his work.This choice is also examined under the broader framework of the discovery,ideological approach and reconstruction of the Minoan civilization in thefirst decades of the 20th century.